2014
DOI: 10.1590/s1678-86212014000300011
|View full text |Cite
|
Sign up to set email alerts
|

Tijolos vazados de solo-cimento produzidos com solo da Região do Arenito Caiuá do Paraná

Abstract: Pesquisas sobre materiais e técnicas de construção que considerem o contexto atual de preservação do meio ambiente e de desenvolvimento socioeconômico regional sustentável estão cada vez ganhando mais espaço na sociedade. Nesse aspecto, cita-se o caso das misturas de cimento ao solo para fins de emprego como material de construção. O presente trabalho tem por objetivo geral avaliar o solo da região do Arenito Caiuá do Noroeste do Paraná com vistas a sua incorporação com o cimento para produção de tijolos de so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Particle size was analyzed as described by Ferrari et al (2014), and the results showed that the texture was sandy (190, 30, and 780 g kg -1 clay, silt, and sand). Soil chemical analysis was conducted in accordance with the methods described by Embrapa (2011 On February 21, eggplant seeds were seeded in polyethylene trays filled with a commercial substrate based on pine bark.…”
Section: Methodsmentioning
confidence: 99%
“…Particle size was analyzed as described by Ferrari et al (2014), and the results showed that the texture was sandy (190, 30, and 780 g kg -1 clay, silt, and sand). Soil chemical analysis was conducted in accordance with the methods described by Embrapa (2011 On February 21, eggplant seeds were seeded in polyethylene trays filled with a commercial substrate based on pine bark.…”
Section: Methodsmentioning
confidence: 99%
“…Em geral, os resultados de resistência deste tipo de tijolos estão em conformidade com outros trabalhos. Ferrari et al [33] estudando tijolos produzidos com solos da região de Arenito Caiuá obtiveram resultados entre 2,0 MPa e 3,2 MPa. Soares et al [34], estudando tijolos com solo de Teresina (Piauí), chegaram a um valor médio de 3,7 MPa.…”
Section: Tijolo De Solo-cimento Produzido Pelas Famílias Na Olaria Co...unclassified
“…Kazmi et al (2016) found that the compressive strength of clay bricks was decreased by incorporating rice husk ash and SCBA into the bricks, and the addition of ash increased material porosity, reducing the strength of the bricks from 8.38 MPa to 5.10 MPa. Ferrari et al (2014) reported that the compressive strength of soil-cement bricks was decreased by 50% by replacing 20% of cement with Engenharia Agrícola, Jaboticabal, v.39, n.1, p.26-31, jan./feb. 2019 SCBA compared with mixtures not containing SCBA, and the minimum strength recommended by the norm was not achieved.…”
Section: Water Absorption Testmentioning
confidence: 99%
“…Other contributing factors for the low compressive strength of the bricks were the mixing of SS and CS and the non-measurement of normative parameters for confirming the feasibility of using SS + CS, including granulometry, liquidity limit, and plasticity limit. According to the soil mixtures used and the respective substitution of these by ash, the sampled materials had similar compositions:  Composition 1: 75% sand, 5% silt, and 20% clay;  Composition 2: 70% sand, 6% silt, and 24% clay;  Composition 3: 58% sand, 9% silt, and 33% clay; Ferrari et al (2014) used a soil containing 78% sand, 3% silt, and 19% clay for producing soil-cement bricks. This soil was prepared according to the recommendations of NBR 6457 without the addition of ash, and compressive strength was higher than the recommended value (2.0 MPa) at 7 days of age.…”
Section: Water Absorption Testmentioning
confidence: 99%